(3Pjd dH GddHGH aj GdCfSGH ddSjhWis - (3eMeO CHj GdYR GdYLejs; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hCaVd GdUdGI hCJe GdJSdje Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3hLQOg JdejP YHOGdQMef GdCTehfj aj SfI (B1089 (3g` ef gGeT fSNJg ef dH GddHGH ddSjhWjs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs